A novel combination of in vitro propagation and hydroponic culture for hybrid cacao (Theobroma cacao) plants - Luis David Vera Pinargote; Elisabeth Jamet; Naga Raju Maddela (Applications in Plant Sciences, 2025)
Abstract Premise Currently, there is a lack of controlled cultivation methods for cacao (Theobroma cacao), a plant species with high commercial value. One major concern is the tendency of cacao plants to accumulate high concentrations of cadmium (Cd), a heavy metal with high toxicity to living organisms. Methods and Results We describe a new two‐step method for the propagation of hybrid cacao plants, consisting of (1) in vitro germination for two weeks, followed by (2) transfer to a vertical hydroponic system for growth under controlled conditions. As a test case, two new cacao hybrids were cultivated in the presence of Cd and showed different levels of tolerance. Conclusions Our simple approach offers a new research direction for the controlled cultivation of cacao plants and can potentially be applied to other plants of agronomic interest. Moreover, this method allows the identification of plants that are resistant to various toxic substances, which could then be used in phytoremediation.